Dataset of concentrations of legacy persistent organic pollutants in fishes and human of the European Arctic Russia - Aksenov, Andrey (Zenodo, 2022)
The dataset presented in this Data descriptor supports “Persistent organic pollutants (POPs) in fish consumed by the indigenous peoples from Nenets Autonomous Okrug” (Lakhmanov et al., 2020).